Plac8 regulates the fibrogenic ability of cardiac fibroblasts in mice with myocardial infarction - Ting Fu; Jianping Gong; Lei Xu; Ningning Ji (All Life)
Cardiac fibroblasts (CFs) are of vital importance for post-myocardial infarction (MI) remodeling. This study explored the role of Placenta specific 8 (Plac8) in MI on the basis of single-cell RNA-Seq (scRNA-Seq) data (GSE136088) and micro-array data (GSE153485). Through bioinformatics analysis, Plac8 was finally identified as a key gene related to fibroblasts. In addition, primary CFs of the neonatal mice were isolated, cultured and treated with hypoxia for in vitro cell model construction. Hydroxyproline assay demonstrated enhanced collagen production in hypoxic CFs, and qRT-PCR revealed increased relative contents of type I and type III collagen (Col1a1 and Col3a1). Western blot showed increased protein expression level of α-smooth muscle actin (α-SMA), and transwell assay and wound-healing assay collectively suggested enhanced cell migration. Moreover, Plac8 was found to be upregulated in hypoxic CFs. Then, after transfection with siNC or siPlac8, it was revealed that down-regulating Plac8 protein expression in hypoxic CFs reduced the levels of collagen secretion, the number of activated CFs and the degree of cell migration, indicating the regulation of Plac8 on hypoxic CFs’ transformation into myofibroblasts, cell migration and collagen deposition. Excessive myocardial fibrosis can cause adverse cardiac remodeling, leading to malignant arrhythmia and even heart failure.